Central Bank Digital Currency: A Catalyst for Indonesian Banking Law Reform - Fajar Al Arif Fitriana, Mohamad Noor; Fauzi, Ahmad; Polem, Azmi (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The rise of virtual money, particularly cryptocurrencies as a means of e-commerce payment, has spurred global interest in Central Bank Digital Currency (CBDC). In Indonesia, however, the absence of a legal framework for CBDC creates a regulatory vacuum, highlighting the urgent need for banking law reform. This study examines the role of CBDC as legal tender, emphasizing its necessity for modernizing Indonesia's financial system. Using a normative juridical approach, supported by primary and secondary data, the research identifies critical gaps in existing legislation, particularly Law No. 7 of 2011 on Currency and Law No. 3 of 2004 on Bank Indonesia. The study proposes three applicable CBDC design models: instrument, ledger, and incentive design. These models address the practical and legal challenges of CBDC implementation. The findings underscore the need for comprehensive legal reform to establish CBDC as a secure, regulated, and universally accepted payment system in Indonesia.